CORPORATE SOCIAL RESPONSIBILITY FROM THE PERSPECTIVE OF RETAIL FOOD CHAINS IN THE CZECH REPUBLIC (Perner's Contacts, 2016)
The corporate social responsibility concept represents voluntary integration of social and environmental aspects to strategic and everyday routine processes and operations of companies. The concept is based on wide participation of important interested parties and communication with these parties. Corporate social responsibility consists of three pillars – an economic pillar, a social pillar and an environmental pillar. This article is focused on information about corporate social responsibility that is commonly available on websites and also in relevant documents provided by the retail food chains in the Czech Republic. These pieces of information are compared by means of content analysis. The content of the released information is evaluated with respect to recommendations provided by the Global Reporting Initiative (GRI) in the sphere of sustainability reporting.
Keywords: corporate social responsibility; food supply chain; retail food chain; sustainability reporting; environmental and social aspects